Exploring professionals’ experiences when choosing graphic symbol sets - Pampoulou, Eliada (My University, 2017)
Purpose - The ongoing development of new graphic symbol sets in conjunction with a lack of literature supporting professionals in choosing the optimum set(s) for their users was the driving force behind this research project. The purpose of this paper is to explore the factors that professionals take into consideration when they choose one graphic symbol set instead of another. Design/methodology/approach - Based on the phenomenology of pedagogy, semi-structured interviews were used with three speech and language therapists (SLTs), three special education teachers, one teacher for pupils with hearing loss, one foundation year teacher and one SENCo/deputy head teacher. Thematic analysis was used to process the data. Findings - The results have shown that when professionals choose a graphic symbol set for their user(s), they focus on the iconicity, the software availability and its features. They are also influenced by any existing graphic symbol policies in the area they work. Training and follow-up support also influence professionals' experiences when choosing graphic symbol sets for their users. Practical implications - Given the limited literature pertaining to the topic of this paper, it is proposed that further research is conducted in order to build the theoretical and practical frameworks upon which professionals (such as SLTs and teachers), symbols developers and academics can base their future work. Originality/value - This research aims to contribute to the scant literature regarding the factors that SLTs take into consideration when choosing a graphic symbol set for their user(s).
Keywords: England; Cyprus; Graphic symbols; Makaton; Picture Communication Symbols; Widgit